Repressive Actions by Authorities in the Raid of a Gay Party in Siwalankerto, Surabaya: A Legal and Human Rights Perspective - Ainina Ayu Kinanti (Media Hukum Indonesia (MHI), 2026)
This study aims to analyze the legitimacy of repressive actions carried out by law enforcement officers in the raid of a gay party in Siwalankerto, Surabaya, from the perspective of criminal law and human rights. The core issue lies in whether such enforcement actions are legally justified or tend to exceed authority by prioritizing public morality over legal certainty. This research uses a normative juridical method with statutory and conceptual approaches, supported by case analysis. The results indicate that law enforcement actions in this case raise serious legal concerns due to the absence of explicit criminal provisions governing such conduct. This condition creates potential overcriminalization and risks violating fundamental human rights, particularly the right to privacy. On the other hand, arguments supporting the raid emphasize the importance of maintaining public order and societal moral values. In conclusion, the legitimacy of repressive actions in this case remains debatable, requiring clearer legal boundaries to ensure that law enforcement does not undermine legal principles and human rights protections.